2006
DOI: 10.1093/brain/awl031
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex plasticity in Parkinson's disease and levodopa-induced dyskinesias

Abstract: Experimental models of Parkinson's disease have demonstrated abnormal synaptic plasticity in the corticostriatal system, possibly related to the development of levodopa-induced dyskinesias (LID). We tested the hypothesis that LID in Parkinson's disease is associated with aberrant plasticity in the human motor cortex (M1). We employed the paired associative stimulation (PAS) protocol, an experimental intervention involving transcranial magnetic stimulation (TMS) and median nerve stimulation capable of producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
232
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(255 citation statements)
references
References 43 publications
22
232
1
Order By: Relevance
“…Other intrinsic differences in protocols used to induce cortical plasticity in humans, e.g., stimulation mode or pulse frequency (Ziemann, 2004), may additionally contribute to differential findings between studies. We chose the PAS protocol (Stefan et al, 2000) for the present study as a frequently used and sensitive tool to investigate cortical plasticity and its relation to age and cognitive function in healthy subjects and neurological patients (Morgante et al, 2006;Weise et al, 2006;Frantseva et al, 2008;Muller-Dahlhaus et al, 2008;Castel-Lacanal et al, 2009;Fathi et al, 2010;Zeller et al, 2010;List et al, 2011List et al, , 2012.…”
Section: Bdnf Val66met and Brain Stimulationmentioning
confidence: 99%
“…Other intrinsic differences in protocols used to induce cortical plasticity in humans, e.g., stimulation mode or pulse frequency (Ziemann, 2004), may additionally contribute to differential findings between studies. We chose the PAS protocol (Stefan et al, 2000) for the present study as a frequently used and sensitive tool to investigate cortical plasticity and its relation to age and cognitive function in healthy subjects and neurological patients (Morgante et al, 2006;Weise et al, 2006;Frantseva et al, 2008;Muller-Dahlhaus et al, 2008;Castel-Lacanal et al, 2009;Fathi et al, 2010;Zeller et al, 2010;List et al, 2011List et al, , 2012.…”
Section: Bdnf Val66met and Brain Stimulationmentioning
confidence: 99%
“…Impaired PAS-induced LTP-like plasticity is typically observed in disorders associated with a dysfunctional dopaminergic system such as Parkinson's disease (Morgante et al, 2006;Ueki et al, 2006;Schwingenschuh et al, 2010) or schizophrenia (Frantseva et al, 2008), or a deficient central cholinergic system such as Alzheimer's disease (Battaglia et al, 2007), whereas exaggerated PASinduced LTP-like plasticity can be observed in states of increased endogenous central cholinergic tone such as dystonia (Quartarone et al, 2003(Quartarone et al, , 2008Weise et al, 2006;Schwingenschuh et al, 2010).…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Indeed, some studies have shown that MEP changes following PAS reach their maximum 30-60 minutes following PAS (Frantseva et al, 2008;Morgante, Espay, Gunraj, Lang, & Chen, 2006). Our choice of measuring MEPs up to 15 minutes following PAS was motivated by the earlier work of Stefan et al (2000), which suggested that the largest changes in cortical excitability occur at approximately this time point, before gradually returning to baseline at 60 minutes post-PAS.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%